A Review of High-Energy X-Ray Diffraction from Glasses and Liquids. (14th November 2012) - Benmore, C. J.
Abstract : This paper summarizes the scientific trends associated with the rapid development of the technique of high-energy X-ray diffraction over the past decade pertaining to the field of liquids, glasses, and amorphous materials. The measurement of high-quality X-ray structure factors out to large momentum transfers leads to high-resolution pair distribution functions which can be directly compared to theory or combined with data from other experimental techniques. The advantages of combining highly penetrating radiation with low angle scattering are outlined together with the data analysis procedure and formalism. Also included are advances in high-energy synchrotron beamline instrumentation, sample environment equipment, and an overview of the role of simulation and modeling for interpreting data from disordered materials. Several examples of recent trends in glass and liquid research are described. Finally, directions for future research are considered within the context of past and current developments in the field.